Secure smart contracts for cloud‐based manufacturing using Ethereum blockchain. Issue 4 (13th October 2020) - Kumar, Ajay; Abhishek, Kumar; Nerurkar, Pranav; Ghalib, Muhammad Rukunuddin; Shankar, Achyut; Cheng, Xiaochun
Abstract: Past international trade practices have been associated with opaque information flows that have hindered traceability and created hurdles in hassle‐free trade. Blockchain and allied technologies have been investigated as a panacea for the problems faced by the Cloud‐Based Manufacturing industry. However, previous literature has focused on limited aspects of a typical Cloud‐Based Manufacturing chain, such as monitoring assets and securing traceability, which is widely neglecting data integrity and data access. To overcome such drawbacks, the current paper proposes secure smart contracts based on the ERC20 interface in a permissioned blockchain with relevant processes and functions to obtain a holistic framework for securing Cloud‐Based Manufacturing operations. The efficacy of the proposed framework was demonstrated on the case study. It was found that critical loopholes in a current supply chain can be overcome using the proposed framework. Additionally, several outlines for future research are outlined. Abstract : The current paper proposes permission Blockchain with relevant processes and functions to obtain a holistic framework for securing the supply chain and logistic operations. The efficacy of the proposed framework was demonstrated in the case study. It was found that critical loopholes in a current supply chain can be overcome using the proposed framework.